Pulmonary drug delivery system: Review - Chaturvedi N.P.; Solanki H. (My University, 2025)
Growing attention has been given to the potential of pulmonary route as an alternative for non-invasive systemic delivery of therapeutic agents.Pulmonary drug delivery can be used as an alternative to oral delivery. These systems can be best utilized for both local and systemic actions.Pulmonary drug delivery is an importantresearch area which impacts the treatment of illnesses including asthma, chronic obstructive pulmonary disease and various other diseases. Inhalation gives the most direct access to drug target. This route can be used to deposit the drug to the target site at high concentration, reducing the amount of drug given to the patient and also help in reducing the systemic side effect and first pass metabolism. In the treatment of obstructive respiratory diseases, pulmonary delivery can minimize systemic side effects, provide rapid response and minimize the required dose since the drug is delivered directly to the conducting zone of the lungs. Generally half of all pharmaceuticals are not soluble in water, but are soluble in lipid. As the lung is able to absorb both water and oil into the tissue, this is not a restriction of pulmonary delivery. Carriers like micro particles, nanoparticles, liposomes can be used in lung targeting.This article focuses on the technologies, mechanism of drug deposition, devices, carriers and recent advances used in pulmonary drug delivery system.